GE_GERICHTE A/1811/2024 vom 30. Januar 2025 - GE Cour de justice (2025)
MAXIME INQUISITOIRE;DROIT D'ÊTRE ENTENDU;MOTIVATION DE LA DÉCISION;CAS DE RIGUEUR | Cst.29.al2; LEI.30.al1.letb; OASA.31.al1; LEI.64.al1.letC; LEI.83.al1